Spectral Functions and Properties of Nuclear Matter. (15th July 2013) - Danilenko, V. A.; Gridnev, K. A.; Kondratyev, A. S.
Abstract : The Green's function method in the Kadanoff-Baym version provides a basic theory for nuclear dynamics which is applicable also to nonzero temperature and to nonequilibrium systems. At the same time, it maintains the basic many-body techniques of the Brueckner theory that makes reasonable a comparison of the numerical results of the two methods for equilibrium systems. The correct approximation to the spectral function which takes into account the widths of energy levels is offered and discussed, and the comparison of the values of binding energy in the two methods is produced.